Population and trend analysis for green turtle (Chelonia mydas) and hawksbill turtle (Eretmochelys imbricata) in Marine Park Centre Redang, Terengganu and Marine Park Centre Rusukan Besar, Labuan, Malaysia - Ghazali, Azizul Fariha; Jamil, Nor Rohaizah (Universiti Putra Malaysia Press, 2019)
This paper highlights basic data collected over the 7 years and 8 years of establishment of the marine turtle hatchery projects in Pulau Rusukan Besar Marine Park Centre (PRBMPC), Federal Territory of Labuan and Pulau Redang Marine Park Centre (PRMPC), Terengganu; Malaysia, respectively. Compiled data were taken from year 2010 until 2017. The within and between season patterns in terms of nest number of the green (Chelonia mydas) and hawksbill (Eretmochelys imbricate) turtles were shown. The population of marine turtles were estimated from the number of nests laid. Total annual nests were used as a crude index of female turtle abundance. Green turtles accounted for 96.18% (1,233 nests laid) of the total nesting recorded while hawksbills accounted for the remaining 3.82% (49 nests laid) in the PRMPC. However, in the PRBMPC 23.58 % (29 nests laid) and 76.42% (94 nests laid) were recorded respectively for the green and hawksbill turtle. 100 % of the nest laid have been incubated using the ex-situ conservation method with the production of 103,929 and 23,558 live green and hawksbill turtle hatchlings respectively. The 8-year average hatching and emergence success rates for green turtles and hawksbills were 87.11 and 88.33%, and 91.56 and 90.69% respectively. This paper provides important information that is fundamental for the understanding of population status to ensure effective conservation measures and management of marine turtles at both marine parks.